2016
DOI: 10.2147/opth.s120414
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes with toric intraocular lenses planned using an optical low coherence reflectometry ocular biometer with a new toric calculator

Abstract: PurposeTo prospectively evaluate postoperative clinical outcomes with implantation of toric intraocular lenses (IOLs) using preoperative keratometry from an optical low coherence reflectometry (OLCR) ocular biometer (Lenstar® LS900) and the built-in Barrett toric calculator.Patients and methodsA prospective observational study recruited one or both eyes of subjects who underwent uncomplicated cataract surgery with toric IOL implantation using OLCR biometery data and the Barrett toric IOL calculator for toric I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 20 publications
1
19
1
Order By: Relevance
“…Höhn et al [12] obtained a mean UIVA of 0.00 logMAR at 12 months after the implantation of the AT LISA trifocal toric IOL. The data presented demonstrate the visual superiority at intermediate distances of the AT LISA tri toric 939MP IOL compared to bifocal toric IOLs [9, 17, 22]. Marques and colleagues [17] found, at 6 months post implantation of a diffractive bifocal IOL, a mean UIVA of 0.18 ± 0.09 logMAR and Shimoda et al [22] reported a mean UIVA of 0.20 ± 0.09 at 70 cm at 3 months post implantation of another bifocal diffractive toric IOL.…”
Section: Discussionmentioning
confidence: 88%
“…Höhn et al [12] obtained a mean UIVA of 0.00 logMAR at 12 months after the implantation of the AT LISA trifocal toric IOL. The data presented demonstrate the visual superiority at intermediate distances of the AT LISA tri toric 939MP IOL compared to bifocal toric IOLs [9, 17, 22]. Marques and colleagues [17] found, at 6 months post implantation of a diffractive bifocal IOL, a mean UIVA of 0.18 ± 0.09 logMAR and Shimoda et al [22] reported a mean UIVA of 0.20 ± 0.09 at 70 cm at 3 months post implantation of another bifocal diffractive toric IOL.…”
Section: Discussionmentioning
confidence: 88%
“…SIA has been emphasized in previous studies as it leads to better visual performance and satis- (Gundersen and Potvin, 2016;Srivannaboon and Chirapapaisan, 2017;Clark, 2018) . The surgical technique is an established factor that in luences SIA (Kawahara et al, 2013;Kwon et al, 2014;Chang et al, 2015;Nikose et al, 2018) .…”
Section: Resultsmentioning
confidence: 99%
“…But facts show that although the value is small, it is not a fixed value, that is, the distribution of PCA cannot be inferred only by measuring the asphericity of the anterior corneal surface 2123. Disregarding PCA potentially underestimates ATR astigmatism (ATRA) and overestimates WTR astigmatism (WTRA), and owing to the posterior surface’s predominant WTR shape that affects the ATRA power, thus correspondingly yield an under-corrected ATRA and over-corrected WTRA 7,10,24,25. The measurement errors of corneal refractive power and astigmatism before cataract surgery will lead to inaccurate IOL degree in surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Koch et al found TCA value is affected by PCA (average-0.3D) 8. PCA potentially decreased TCA in with-the-rule (WTR) astigmatism cases or increased it, as observed in against-the-rule (ATR) cases1,810; discounting PCA could result in miscalculated astigmatism, as in WTR cases overestimated by 0.5–0.6D and ATR underestimated by about 0.2–0.3D 5. A 7.4°±10.3° axis error has also been documented, reportedly caused by ignoring PCA 11.…”
Section: Introductionmentioning
confidence: 99%